Does therapy with immunosuppressive drugs improve gastrointestinal symptoms in patients with systemic sclerosis? - Oliver Distler; Cosimo Bruni; Suzana Jordan; Carina Mihai; Muriel Elhai; Rucsandra Dobrota; Alexandru Garaiman; Mike Oliver Becker; Lea Stamm; Sherif Ismail; Norina Zampatti; Aurora Maria Tatu (RMD Open)
Objectives While important progress was made regarding the treatment of systemic sclerosis (SSc), there is still no evidence-based disease-modifying treatment available for SSc-related gastrointestinal (GI) manifestations. We aimed to identify an association between immunosuppressive therapy and the the severity of GI symptoms, measured by the University of California at Los Angeles/Scleroderma Clinical Trial Consortium Gastro-Intestinal Tract instrument 2.0 (GIT).Methods We selected patients with SSc who had at least two visits (further referred to as ‘baseline’ and ‘follow-up’) with completed GITs, within an interval of 12±3 months. The study outcome was the GIT score at follow-up. We used multivariable linear regression with the following covariates: immunosuppressive therapy during observation, immunosuppressive therapy before baseline, baseline GIT and several baseline parameters selected by clinical judgement as potentially influencing GI symptoms.Results We included 209 SSc patients (82.3% female, median age 59.0 years, median disease duration 6.0 years, 40 (19.1%) diffuse cutaneous SSc, median baseline GIT 0.19). Of these, 71 were exposed to immunosuppressive therapy during the observation period, and, compared with unexposed patients, had overall more severe SSc and a higher prevalence of treatment with proton pump inhibitors. In multivariable linear regression, immunosuppressive therapy during the period of observation and lower baseline GIT scores were significantly associated with lower (better) GIT scores at follow-up.Conclusion Immunosuppressive treatment was associated with lower GIT scores in our cohort, which suggests the potential effects of immunosuppressants on GI manifestations in patients with SSc, requiring confirmation in prospective randomised clinical trials.